Analisis Keberhasilan Inseminasi Buatan (IB) Ternak Sapi Berdasarkan Karakteristik Inseminator di Kabupaten Kerinci - Lusi Amidia; Fachroerrozi Hoesni; Bayu Rosadi (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of internal and external inseminator characteristics on the success of IB in Kerinci Regency. This research was conducted on December 12, 2020 to January 6, 2021. The objects observed in this study were all inseminators at each IB post in Kerinci Regency.The data obtained from this study are primary data and secondary data. The data were analyzed using Stepwise Multiple Regression analysis. The results of the analysis show that the success of artificial insemination in Kerinci Regency is good, this can be seen from the S/C value per inseminator of 1.69.The influence of internal characteristics (length of work, training intensity, accuracy, technical ability of straw management and estrus detection) and external (distance from house to work area, supporting facilities, condition of post IB, sanitation of tools and fittings) has an effect (P>0.05). Meanwhile, internal characteristics (responsibility) and external (voluntary rewards) have no effect (P>0.05) on the success of IB in Kerinci Regency. Based on this research, it can be concluded that not all internal and external characteristics affect the success of IB in Kerinci Regency.